2018
DOI: 10.1111/jocd.12524
|View full text |Cite
|
Sign up to set email alerts
|

Review and clinical experience exploring evidence, clinical efficacy, and safety regarding nonsurgical treatment of feminine rejuvenation

Abstract: As this is an evolving medical field, clinical evidence often lacks robustness. Studies and clinical experience suggest that feminine genital rejuvenation using energy-based devices seems an attractive option for patients with mild-to-moderate medical conditions. The treatment can be safely and effectively delivered by trained staff as part of the comprehensive care, that is, currently available to women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 28 publications
0
43
0
2
Order By: Relevance
“…Non‐ablative laser therapy has also gained interest in various medical conditions, such as GSM, urinary incontinence, and other medical conditions . In human soft tissue, the 2940 nm erbium yttrium‐aluminum‐garnet medium (Er:YAG) laser in the non‐ablative thermal mode has been shown to stimulate deep collagen remodeling and improve tightness and elasticity of the treated area .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Non‐ablative laser therapy has also gained interest in various medical conditions, such as GSM, urinary incontinence, and other medical conditions . In human soft tissue, the 2940 nm erbium yttrium‐aluminum‐garnet medium (Er:YAG) laser in the non‐ablative thermal mode has been shown to stimulate deep collagen remodeling and improve tightness and elasticity of the treated area .…”
Section: Discussionmentioning
confidence: 99%
“…Increasing in prevalence, vaginal rejuvenation has been characterized as a laser and energy‐based technique (ablative and non‐ablative lasers, and radiofrequency devices) to optimize sexual function and alleviate genitourinary syndrome of menopause (GSM)‐related symptoms in women. It has also been offered to those experiencing pelvic floor dysfunction, urinary incontinence, and dissatisfaction with vulvovaginal anatomy . Current literature lacks data supporting the efficacy of these procedures and characterizing safety profiles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent RF studies showed an increase in the small nerve fiber density in the papillary dermis ( Gold et al, 2018 ; Table 3 ). Posttreatment biopsy tests have demonstrated neocollagenesis and neoelastogenesis in the submucosa after RF ( Leibaschoff et al, 2016 ; Figure ).…”
Section: Noninvasive Modalitiesmentioning
confidence: 99%
“…The aim of treatment is to heat vaginal/vulvar epithelium to approximately 40-45°C for a defined treatment time, with each zone being treated for 3-5 minutes, for a total time of 25-30 minutes per treatment session [23]. These sessions may be repeated at 4-6 week intervals [24]. Ultrasound gel is needed during the treatment process.…”
Section: Treatment Of Genitourinary Syndrome Of Menopausementioning
confidence: 99%